The Politics of Media Infrastructure: Mobile Phones and Emergent Forms of Public Communication in Papua New Guinea. Issue 1 (17th February 2020) - Foster, Robert J.
ABSTRACT: Recent work in anthropology proposes that the ethnographic study of infrastructure offers a productive way to think about how states and corporations, citizens and consumers, all define their relations and obligations to each other. This article considers the politics of media infrastructure in Papua New Guinea (PNG) by tracing the moral economy of mobile phones. It focuses on (1) how mobile phone users have taken to social media to express dissatisfaction with the dominant mobile network operator, Digicel, a privately owned foreign company; and (2) how the PNG state has attempted to regulate the use of mobile phones and social media through cybercrime legislation and registration of Subscriber Identity Modules (SIM cards). Consideration of these two issues – matters of concern that gather publics around them – enables an assessment of the promise of improved telecommunications and social media, in particular, to make government in PNG more accountable and transparent.